Assess The Effectiveness Of Skills In Sending And Beating The Overwhelming According To The Analytical Program Using The Computer On Volleyball Players (Journal of Pharmaceutical Negative Results, 2022)
The significant development that occurs in sports, including volleyball, makes the developed countries resort to the development ofmodern skill methods in confronting the opposing team, and its conviction that these methods represent the most important aspect ofthe game. In addition to the high physical fitness required by the game, it should be taken care of. It makes it easier for the player orteam to know the offensive or defensive tactical aspects of the opposing team. This skill development came using modern scientificmethods in the measurement and technical analysis performed by the players, as the analysis during the matches gives more credibilitythan in training. So, modern devices are used in photography and in the computer, which has become of great importance in the processof skill analysis for players.Aim: Effectiveness analysis of the two types of serving skill (smashing from jumping - fluttering serving from jumping).Method: Population of study: Players from the Al-Ahly volleyball club (women). Duration of the study: The time between (2/5/2022and 31/5/2022).The researcher identified the research community represented by the players of the Al-Ahly volleyball team that participated in theAfrican Championship held in Tunisia and their number (13), which represents (100%) of the research community.Conclusions: There is a weakness in the skill of serving in the ace's quality and flutter of the Al-Ahly team players. The effectivenessof the center (2) is better than the impact from the center (4). Variation in the effectiveness ratios for the crushing strike from a position(1) between one match and another according to the effectiveness team.Recommendations: Training in the accuracy, concentration, and speed of hitting the ball in the aces and flutter to increase theeffectiveness. Introducing fun and suspense in training transmitter types, as well as increasing motivation. A lot of friendly matcheswith high-level teams develop the skill level of the players.